A formação na linha de fogo : videogames de guerra e a psique danificada - Guimaro, Maria Luiza Oliveira (2010)
The objective of this thesis was the formative dimension of the youth in the contemporary world. We noticed that we could reflect upon this dimension through the following inquisition: What makes the youth be uninterested by the ―school seat‖, and trade them for ―Lan Houses seats‖. This problem leads us to think about some aspects of the current culture we emphasize here the overuse of war videogames which seem to be promoting identity and subjective constitution of the youth, instigating them to compulsive and addictive behavior. Thus, the present study aims at the subjectivity of the youth through videogames, especially the war ones, which seem to contribute to a formative harm in the subjects. In order to develop this argument, we need to reflect upon their status quo, the singularities, socialization, and consequently, the construction of their identity in the contemporary world. Our hypothesis, then, suggests that current teenagers are attached to undifferentiated constitution of the social fabric, heteronomously, which results in a rupture to the tendency to extinguish the frontiers between the public and the private, the childhood and the adulthood, the virtual and the real, the formative function of education and its appropriation by the industry. This analysis is also based on the idea that the traditional educational grounds family and school now share this responsibility with other institutions as a means to education. When observing, then, a new structure in the socialization field, we search for a relational perspective of analysis between these grounds, in order to understand the specificity of the identity building processes of the subjects in the current world. Aiming at measuring the current forms of the constitution of this subjectivity, we also resorted to psychoanalyses principles. The loss of authority in the family and by the teacher, mentioned a long time ago by Hannah Arendt, who referred to the allurement of the socialization in modern mass societies, resulting in the true fraud of the public life, and consequently, the public role of the school. One could infer that the decline of authority resides in the psychic field, in the form of a type of pathologization of the idealization (that is, there is no one to be admired), which is affecting the processes of secondary identification. Moreover, it may be contributing in teenage hood seriously shaking its narcissist basis (reinforcing these vices and addictive behaviors). Taking into account these perspective in the process of the subjectivities studied, a tendency to a reconfiguration of the psychic instances may be taking place as a consequence of the changes triggered by the late capitalism and by the changes occurred in paternal, family and school authorities, whose determinants seem to indicate a tendency to addictive behaviors (which are here understood through the heteronomic dependency of the subjects in the imaginet means of entertainment), as personality builders. The analysis of such behaviors may also indicate how much the youth simulate in their bodies and its relation to the extreme tendencies of the society, as a compulsion to repetition.